Establishing Standard Methodologies To Improve The Production Rate Of Assembly Lines Used For Low Added-Value Products - Rosa, Conceição (2020)
Global competitiveness, mainly in the automobile sector, requires a constant focus on products and process innovation in order to provide consumers with a large variety of products of an excellent quality and at a low cost. In line with this philosophy, the study undertaken of the work method and its inherent activities has pointed to time measurement as a support tool of great potential in the optimization of the production process. The present case study aims to optimize the production process of an assembly line dedicated to the manufacture of control cables for the automotive industry. The ultimate objective was to adjust the output of the current line to that of the initial budget. By mapping all the activities and measuring the time spent on each of these, one was able to analyze the existing problems and inefficiencies. Subsequently, through the use of Lean tools and methodologies, one managed to find viable solutions, which resulted in a significant increase in productivity. The solutions implemented have allowed for an increase in line output of 43%, thus setting it within the values considered in the budget. One also achieved a reduction of 30% in assembly line use, which allowed for the addition of new product references on the assembly line in question. Since these gains are considerable for the company, the same methodology was standardized so that it could be applied to other assembly lines.